Long amplicons as a tool to identify variable regions of ribosomal RNA for improved taxonomic resolution and diagnostic assay design in microeukaryotes: using ascetosporea as a case study - Hooper, Chantelle; Ward, Georgia M.; Foster, Rachel; Skujina, Ilze; Ironside, Joseph E.; Berney, Cédric; Bass, David (Frontiers in Ecology and Evolution, 2023)
There is no universally appropriate basis for delimiting species in protists, including parasites. Many molecular markers used for species delimitation are part of the ribosomal RNA (rRNA) array, with different regions of the array being used for different parasitic protist taxa. However, little is known about sequence variability across the rRNA in most organisms, and there is no standard threshold at which divergence in the sequence of a particular gene can be used as a basis for species delimitation. Here we demonstrate a method to generate the full rRNA array of parasitic protists by amplification of the array in two long, overlapping fragments followed by Illumina and Nanopore sequencing to produce high quality assemblies, to determine variations in sequence variability across the array. We apply this approach to two pairs of closely related ascetosporean parasites of crustaceans and molluscs (respectively Paramarteilia canceri/P. orchestiae and Marteilia cochillia/M. cocosarum (Rhizaria; Endomyxa; Ascetosporea)) and Bonamia ostreae and demonstrate how full-length rRNA sequences can be used to determine regions of the rRNA array that are most discriminatory, and robustly differentiate between species in combination with other lines of evidence. Phylogenetic analyses of the transcribed regions of the rRNA array demonstrate maximal support for, and separation of, all four parasites species. Sliding window global alignment analysis determined the regions of the rRNA array that had the most consistent nucleotide differences between the closely related parasites in a 1 kb region of the array. For Paramarteilia, this region was a combined internal transcribed spacer 1-5.8S-internal transcribed spacer 2 alignment, and for Marteilia, it was the external transcribed spacer. Phylogenetic analysis of these regions were able to recover the respective species, demonstrating that these regions could be used for improved diagnostic PCR assays. Our method could be adapted to quickly generate sequence data and determine regions more suitable for diagnostic assays for a wide diversity of parasite groups. It also allows the generation of sequence data for regions of the rRNA not commonly studied (e.g. regions of the intergenic spacer), thus enabling research into their suitability as marker regions.